A small step towards empowering communities: assessing and educating stroke symptoms, risk factors and treatment access: a cross-sectional study in two villages of South India - Pokalkar, Apeksha; Pokalkar, Ayushi (International Journal of Research in Medical Sciences, 2025)
Background: Stroke is a major preventable cause for disability and death. It has a host of modifiable risk factors. Management of stroke is getting revolutionised. The benefits of these recent advances are not passed to the public more so to the rural folks because there is lack of awareness of stroke symptoms and therapeutic options available for them. Methods: In a door-to-door survey, subjects were randomly selected to take a questionnaire based on the stroke awareness questionnaire published in the literature. Measures were taken to prevent group answering. Subsequently all subjects in small groups were explained details of stroke symptoms, related risk factors and the various treatment options available to them in the vicinity. The data so acquired was tabulated and analysed statistically. Results: Most of the subjects were aware of stroke symptoms and risk factors associated with it. But they preferred local native medicines and were not aware of recent treatment modalities. Conclusions: Most of subjects in the rural area were unaware of recent treatment modalities for stroke in spite of being aware of its manifestations and associated risk factors. There is strong need to educate rural population about stroke treatment.